Effect of heavy metals on oxidative markers and semen quality parameters in HF crossbred bulls - CHAND, N; TYAGI, S; PRASAD, R; DUTTA, D; SIROHI, A S; SHARMA, A; TYAGI, R (The Indian Journal of Animal Sciences, 2019)
The study was conducted to assess the effect of toxic heavy metals on seminal antioxidants, trace minerals and semen quality parameters in crossbred breeding bulls. Semen samples were collected from breeding bulls (82) maintained at bull rearing unit of the institute. Toxic heavy metals (Pb and Cd), trace minerals (Zn, Cu, Co and Fe) and oxidative stress markers (SOD, catalase and MDA) were determined in semen samples of breeding bulls. Sperm motility and concentration were measured in fresh ejaculates. Significant levels of Pb (0.23Â±0.006 Î¼g/ml) and Cd (0.11Â±0.005 Î¼g/ml) were detected in semen samples of breeding bulls. On analysis of the data between good and poor bull categories, significantly higher concentration of Pb and Cd was present in semen samples of poor bulls as compared to good bulls. There was significantly higher malondialdehyde (MDA) and low superoxide dismutase (SOD) and catalase in seminal plasma of poor bulls compared to good bulls. A significant decrease in Zn and Cu was observed in poor bulls as compared to good bulls. Cobalt and iron values did not show any significant variation between good and poor quality bulls. On correlation analysis, lead and cadmium showed significant negative correlation with Zn, Cu, SOD, catalase, motility and sperm concentration while significant positive correlation was seen with MDA respectively. The study concludes that increased Pb and Cd in bull semen may increase the risk of seminal oxidative stress development and a subsequent reduction in male fertility.